2016
DOI: 10.1111/epi.13602
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the anticonvulsant lacosamide in experimental and human epilepsy via selective effects on slow Na+ channel inactivation

Abstract: SUMMARYObjective: In human epilepsy, pharmacoresistance to antiepileptic drug therapy is a major problem affecting~30% of patients with epilepsy. Many classical antiepileptic drugs target voltage-gated sodium channels, and their potent activity in inhibiting high-frequency firing has been attributed to their strong use-dependent blocking action. In chronic epilepsy, a loss of use-dependent block has emerged as a potential cellular mechanism of pharmacoresistance for anticonvulsants acting on voltage-gated sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…We observed quantitatively maintained effects of S‐Lic not only on slow inactivation in experimental epilepsy, but also on sodium channels in granule cells obtained from epilepsy surgical specimens. This is similar to the maintained activity of lacosamide on slow inactivation and use‐dependent block in chronic experimental and human epilepsy that was observed in a previous study . In addition, we have shown that the maintained activity also extends to cortical areas, which also display pathological changes in chronic epilepsy models …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We observed quantitatively maintained effects of S‐Lic not only on slow inactivation in experimental epilepsy, but also on sodium channels in granule cells obtained from epilepsy surgical specimens. This is similar to the maintained activity of lacosamide on slow inactivation and use‐dependent block in chronic experimental and human epilepsy that was observed in a previous study . In addition, we have shown that the maintained activity also extends to cortical areas, which also display pathological changes in chronic epilepsy models …”
Section: Discussionsupporting
confidence: 89%
“…Similar effects are shared by some other AEDs. Lacosamide also exerts effects on slow inactivation in different types of neurons . Moreover, as seen for S‐Lic, lacosamide also shifts the voltage dependence of slow inactivation in a hyperpolarizing direction as a major effect, whereas other effects on slow inactivation were small .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations